2019
DOI: 10.1038/s41467-019-08581-8
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal non-canonical NFκB signaling shapes the local and systemic immune response

Abstract: Microfold cells (M-cells) are specialized cells of the intestine that sample luminal microbiota and dietary antigens to educate the immune cells of the intestinal lymphoid follicles. The function of M-cells in systemic inflammatory responses are still unclear. Here we show that epithelial non-canonical NFkB signaling mediated by NFkB-inducing kinase (NIK) is highly active in intestinal lymphoid follicles, and is required for M-cell maintenance. Intestinal NIK signaling modulates M-cell differentiation and elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 70 publications
(95 reference statements)
4
57
0
Order By: Relevance
“…noncanonical NF-kB signaling in assisting M-cell development, we used lentiviruses to target NF-kappa-B-inducing kinase (NIK; encoded by MAP3K14) in human enteroids. Consistent with a recent report of NIK participation in intestinal lymphoid follicle formation, 26 genetic depletion of MAP3K14 led to reduced M-cell numbers by staining ( Figure 3B), suggesting that LT-NIK-RelB signaling is critical to efficient M-cell differentiation.…”
Section: Resultssupporting
confidence: 92%
“…noncanonical NF-kB signaling in assisting M-cell development, we used lentiviruses to target NF-kappa-B-inducing kinase (NIK; encoded by MAP3K14) in human enteroids. Consistent with a recent report of NIK participation in intestinal lymphoid follicle formation, 26 genetic depletion of MAP3K14 led to reduced M-cell numbers by staining ( Figure 3B), suggesting that LT-NIK-RelB signaling is critical to efficient M-cell differentiation.…”
Section: Resultssupporting
confidence: 92%
“…NF-κB is a pivotal regulator of both innate and adaptive immunity within the TIME. [30][31][32] Thus, we further investigated whether the PI3K/Akt/ NF-κB signaling pathway was also involved in the immunomodulatory effect induced by low-dose chemotherapy. Consistent with this assumption, results from FACS data analysis revealed that the CDDP-induced or GEM-induced increases in PD-L1, MHC class I, HLA-A/B/C, and cytoplasmic HMGB-1 expression were abrogated in cells pretreated or co-incubated with BAY 11-7082 (NF-κB inhibitor), LY294002 (PI3K inhibitor), or MK2206 (Akt inhibitor), although to different extents (figure 1C-N).…”
Section: Resultsmentioning
confidence: 99%
“…The NF-κB signaling pathway is a key mediator of cytokine and chemokine transcription and plays a central role in the host response to infection by microbial pathogens. 29 NF-κB essential modulator binds to M1-linked Ub chains at the receptor signaling complex, enabling inhibitor of NF-κB kinase α and β (IKKα/β)-mediated phosphorylation and subsequent proteasomal degradation of NF-κB inhibitor α (IκBα) and nuclear translocation of gene-specific transcription factors. 30 S. typhimurium exploits NLRP12-dependent innate immune signaling to suppress host defenses during infection that S. typhimurium induced NLRP12-mediated inhibition of NF-κB by targeting phosphorylation of IκBα in mice.…”
Section: Discussionmentioning
confidence: 99%